2010
DOI: 10.1111/j.1462-2920.2009.02098.x
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate and limits to photosynthesis in a diverse community of hypolithic cyanobacteria in northern Australia

Abstract: Hypolithic microbes, primarily cyanobacteria, inhabit the highly specialized microhabitats under translucent rocks in extreme environments. Here we report findings from hypolithic cyanobacteria found under three types of translucent rocks (quartz, prehnite, agate) in a semiarid region of tropical Australia. We investigated the photosynthetic responses of the cyanobacterial communities to light, temperature and moisture in the laboratory, and we measured the microclimatic variables of temperature and soil moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 54 publications
5
69
1
Order By: Relevance
“…Overall about 70-80% of variance remained unexplained. Certainly, this is partly due to the fact that we introduced the environmental effect using a relatively broad approximation (climate categories based upon long-term mean annual temperature and precipitation), which ignored any unmeasured local environmental drivers that may be involved in determining community structure (for example, see Tracy et al, 2010). However, given previous studies on these communities that showed hypoliths develop independently of the surrounding soil (Warren-Rhodes et al, 2006; Pointing et al, 2007Pointing et al, , 2009Tracy et al, 2010) owing to the specific microclimatic conditions of rocks, and that climate and continent were independent of spatial patterns observed, it is likely that a large amount of this variation is due to environmental (for example, see Dornelas et al, 2006;Pointing et al, 2009) and/or demographic stochasticity (sensu Hubbell, 2001 andTilman, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall about 70-80% of variance remained unexplained. Certainly, this is partly due to the fact that we introduced the environmental effect using a relatively broad approximation (climate categories based upon long-term mean annual temperature and precipitation), which ignored any unmeasured local environmental drivers that may be involved in determining community structure (for example, see Tracy et al, 2010). However, given previous studies on these communities that showed hypoliths develop independently of the surrounding soil (Warren-Rhodes et al, 2006; Pointing et al, 2007Pointing et al, , 2009Tracy et al, 2010) owing to the specific microclimatic conditions of rocks, and that climate and continent were independent of spatial patterns observed, it is likely that a large amount of this variation is due to environmental (for example, see Dornelas et al, 2006;Pointing et al, 2009) and/or demographic stochasticity (sensu Hubbell, 2001 andTilman, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Our data demonstrate that patterns generally interpreted as indicative of the presence of niche partitioning and non-neutral processes (for example, convergence due to relatively homogeneous environments) vary on a global biogeographical scale (continent) and also between phototrophic and heterotrophic bacteria within a given community. Given that the commonly encountered phyla in hypolithic communities include known desiccationtolerant taxa, this implies that most populations may withstand the high level of demographic stochasticity due to the patchiness of the environment in hyperarid deserts (Pointing et al, , 2009Warren-Rhodes et al, 2007;Tracy et al, 2010). Further, they may opportunistically react to the environmental stochasticity determined by rapid and extreme changes in temperature and water availability.…”
Section: Desert Microbial Community Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…However, whereas altitudinal stratification of higher plants is driven principally by temperature, our data suggest that the principal drivers for hypolithic community stratification in Miers Valley are complex. In hot deserts, both soil water content and temperature dictate the limits of diversity (Pointing et al 2007) and metabolic activity (Tracy et al 2010) and presumably community development processes, and these are likely also the principal drivers of biological processes in cold deserts such as Miers Valley. Open Access This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited.…”
Section: Resultsmentioning
confidence: 99%
“…In some hot arid deserts, hypoliths are colonized only by Chroococcidiopsis sp. (Warren-Rhodes et al 2007), whilst in others, a more diverse range of taxa have been identified (Tracy et al 2010). Polar hypolithons comprise a relatively diverse cyanobacterial assemblage comprising various Oscillatoriales, Aphanocapsa, Aphanothece, Chroococcidiopsis and Gloeocapsa morphotypes (Broady 1981(Broady , 2005Cockell and Stokes 2004).…”
Section: Introductionmentioning
confidence: 99%